Pistoning assessment in lower limb prosthetic sockets - Eshraghi, Arezoo; Abu Osman, Noor Azuan; Gholizadeh, Hossein; Karimi, Mohammad Hossein; Ali, Sadeeq (SAGE Publications, 2012)
BACKGROUND: One of the main indicators of the suspension system efficiency in lower limb prostheses is vertical displacement or pistoning within the socket. Decreasing pistoning and introducing an effective system for evaluating pistoning could contribute to the amputees' rehabilitation process. OBJECTIVES: The main objective of this study was to review existing research studies that examine the occurrence of pistoning in lower limb prosthesis with different techniques in static (standing) and dynamic (walking and jumping) positions. STUDY DESIGN: Literature review. METHODS: Keywords related to slippage, suspension, pistoning and vertical movement in lower limb prosthetics were used to search the literature available in PubMed, ScienceDirect, Web of Science and Google Scholar databases. Sixteen articles were selected for further analysis according to the selection criteria. RESULTS: The following methods have been used to measure the occurrence of pistoning in prosthetic limbs: radiological methods, photographic technique, motion analysis system, sensor and spiral computerized tomography (CT). Pistoning was measured both in standing and walking. CONCLUSIONS: The results of this review reveal that further research is needed to develop and evaluate easy, accurate and safe methods of measuring pistoning. Future studies should provide a gold standard for the acceptable range of pistoning in a prosthetic socket.